O custo zero numa abordagem duchampiana panaceia da ideia no processo de criação artística oficina de artes 2018 - Duarte, Luísa (2019)
The purpose of this project is to allow students to acquire and develop a conceptual view of the artistic object using the individual artistic perception and sensibility present in each of them. Through an introspective vision of their daily lives they will seek new relationships between memory and the object, allowing them to develop and speed up the creative process that is inherently required in any professional area